2018
DOI: 10.5798/dicletip.497923
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect of an electromagnetic field generated by a high voltage power line on rat spermatogonia cells

Abstract: Methods: In the study, 64 rats were divided into eight equal groups (n: 8). In experiments lasting 26 and 52 days, the following groups were used: High voltage (HV), HV + Ganoderma lucidum (GI), HV + Melatonin (MEL), and Shamcontrol. MEL (10 mg/kg) was administered intraperitoneally and GI (20 mg/kg) as oral lavage. Extremely low frequency electric (80.3 V/m) and magnetic fields (2.48 µT) were applied for eight hours per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Ganoderma lucidum, also known as lingzhi in China, yeongji in Korea, and reishi in Japan, is a medicinal mushroom. For thousands of years, these fungi have been utilized to cure and prevent a variety of ailments 4 . Studies have shown that the compounds it contains have very serious medical effects 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma lucidum, also known as lingzhi in China, yeongji in Korea, and reishi in Japan, is a medicinal mushroom. For thousands of years, these fungi have been utilized to cure and prevent a variety of ailments 4 . Studies have shown that the compounds it contains have very serious medical effects 5 .…”
Section: Introductionmentioning
confidence: 99%